The cost of transcatheter aortic valve implantation according to different access routes - Eliana Bittar; Valéria Castilho (SciELO, 2017)
Abstract OBJECTIVE Identifying the average direct cost of TAVI (Transcatheter Aortic Valve Implantation) for the different access routes. METHOD This is a research with a quantitative, exploratory and descriptive approach carried out in a government teaching hospital in the state of São Paulo. RESULTS The average direct cost of TAVI procedures by the access routes resulted in R$82,826.38 (transfemoral route), R$79,440.91 (transaortic route) and R$78,173.41 (transapical route). The transcatheter valve cost represented a percentage variation between 78.47% and 83.14% of the total cost of the procedure. The Kruskal-Wallis test was used and presented a statistically significant difference between the three access routes: p=0.008. The Bonferroni test showed a difference in the association between transfemoral and transapical routes, while no statistically significant difference was observed in association with the transaortic route. CONCLUSION The results are important for formulating adequate funding policies for the hospital network and understanding the costs according to the route facilitates rationalizing resources in order for them to be guaranteed for patients who present surgical contraindication to the valve implant.